Economic development and structural change in India - Narayana, N.; Clark, Colin Kuznets, Simon Hoffmann, W.G. Chenery, H.B. (New Delhi Discovery Pub. House, 1990)
): India in Economic policy -- Industrial promotion -- Economic growth and development, structural changes and its governing factors, change in industrial distribution of labour force, change in industrial structure of net domestic product, trends in pattern of industrial investment of public and private sectors, industrialisation, structural change in industry, impact of industrialisation on foreign trade
Keywords: Structural change -- India -- Economic development; Economic development -- India -- Economic Policy & planning